2022
DOI: 10.1186/s12909-022-03219-8
|View full text |Cite
|
Sign up to set email alerts
|

Students’ perception of educational environment based on Dundee Ready Education Environment Measure and the role of peer mentoring: a cross-sectional study

Abstract: Objective The curricular reform at Tehran University of Medical Sciences (TUMS), Iran, has been implemented since 2011 when peer mentoring program started. The program is believed to have a crucial role in students’ perception of the educational environment (EE). We aimed to determine how students perceive the educational environment and compared the mentees and non-mentees’ perception of EE. Methods A cross-sectional descriptive study was conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 53 publications
3
4
0
Order By: Relevance
“…This result agrees with most studies conducted in different health specialties in different countries [17][18][27][28]30]. Recently, Serrano et al [75] assessed the educational environments in dental colleges in the Netherlands, and Behkam et al [24] investigated medical colleges at the Dundee University Medical School; both studies recorded slightly higher DREEM scores than the scores in the current review. Another study, performed by Hernández-Crespo et al [17] in Spain, indicated that the overall DREEM score of the educational environment among dental colleges students was "more positive than negative" in different academic years of 2010-2011, 2013-2014, 2014-2015, and 2015-2016.…”
Section: Overall Value Of Dreemsupporting
confidence: 91%
See 2 more Smart Citations
“…This result agrees with most studies conducted in different health specialties in different countries [17][18][27][28]30]. Recently, Serrano et al [75] assessed the educational environments in dental colleges in the Netherlands, and Behkam et al [24] investigated medical colleges at the Dundee University Medical School; both studies recorded slightly higher DREEM scores than the scores in the current review. Another study, performed by Hernández-Crespo et al [17] in Spain, indicated that the overall DREEM score of the educational environment among dental colleges students was "more positive than negative" in different academic years of 2010-2011, 2013-2014, 2014-2015, and 2015-2016.…”
Section: Overall Value Of Dreemsupporting
confidence: 91%
“…After 2020, 40%, 20%, and 16% of publications were for dental colleges, applied medical science colleges, and medical colleges, respectively; these values were considerably lower compared with the percentage of articles published before 2020. Other systematic reviews by Behkam et al [24] and Farooqi et al [27] arrived at the same conclusions. Miles et al [15] used studies before 2010, and their review is in parallel with the percentage of studies in the current paper, as presented in Table 3 and Figure 2.…”
Section: Publication Years Rr and Gender Ratiosupporting
confidence: 57%
See 1 more Smart Citation
“…Items with mean scores of less than two should be closely considered. Except for negative items mentioned, a higher score means better interpretation [17, 18].…”
Section: Methodsmentioning
confidence: 99%
“…Items with mean scores of less than two should be closely considered. Except for negative items mentioned, a higher score means better interpretation [17,18].…”
Section: Outcome Measurementmentioning
confidence: 99%